Number of retained radiopaque markers on a colonic transit study does not correlate with symptom severity or quality of life in chronic constipation. Issue 5 (18th December 2017) - Staller, K.; Barshop, K.; Ananthakrishnan, A. N.; Kuo, B.
Abstract: Background: Ingestion of radiopaque markers (ROM) is frequently used to determine colonic transit in chronic constipation. Although ≥20% of retained markers at 5 days defines slow‐transit constipation, some clinicians use the number of retained markers to determine disease severity. Methods: We assembled a cross‐sectional cohort of patients presenting for evaluation of chronic constipation who underwent transit testing by ROM and completed validated symptom severity and quality‐of‐life (QOL) measures. We performed a correlation analysis to determine whether there was an association between number of retained markers and symptom severity and QOL. Key Results: Among 159 patients undergoing evaluation for chronic constipation, there was poor correlation between the number of retained markers and symptom severity ( R  =   .09, P  =   .25) and QOL. Among the 55 patients with slow‐transit constipation defined by ≥5 retained markers retained on day 5, there were similarly poor correlations between symptom severity ( R  =   .17, P  =   .21) and QOL ( R  =   .07, P  =   .60). Excluding patients with irritable bowel syndrome and outlet obstruction by balloon expulsion testing did not materially alter our results, nor did a multivariable analysis controlling for demographic and psychiatric confounders. Conclusions and Inferences: Among patients with chronic constipation, number of retained markers on a ROM colonic transit study does not correlate with measures of symptom severity or QOL. Clinicians should be cautious about overinterpreting ROM transit testing. Abstract : Retention ≥20% of retained markers at 5 days defines slow‐transit constipation in a radiopaque marker (ROM) study, but some clinicians use the number of retained markers as a surrogate for disease severity. We found no correlation between number of retained ROMs and symptom severity or quality of life in a cohort of patients presenting for evaluation of chronic constipation. The results of this study serve as a caution against the overinterpretation of ROM transit testing in chronic constipation.